Improving English Speaking Proficiency in Language Learners: The Impact of the Montessori Method Using Anki Digital Flashcards - Deli, Nala Puti; Wahyuni, Resty; Niswa, Khairun (Journal of English Language and Education, 2025)
The present study evaluates how the integration of the Montessori Method and Anki Digital Flashcards influences the English speaking proficiency of first-year junior high school students at Darul Ulum School, Thailand. A one-group pretest-posttest quasi-experimental approach was utilized with 20 students participating.The intervention combined experiential, student-centered activities based on the Montessori approach with the digital learning features of Anki, which utilizes spaced repetition to enhance vocabulary retention and pronunciation. Data were collected through oral pretests and posttests, focusing on three indicators: vocabulary, fluency, and pronunciation. The findings revealed a notable improvement in the mean score, rising from 79.55 in the pretest to 90.00 in the posttest, resulting in a mean gain of 10.45 points. Statistical analysis using a paired t-test indicated that this improvement was statistically significant (p = 0.001). Observations indicated that students became more confident, fluent, and accurate in their spoken English. The integration of Montessori’s interactive methods with Anki’s digital repetition system created a more active, engaging, and inclusive learning environment. This study concludes that the combined approach is highly effective in enhancing speaking skills for beginner-level EFL learners and offers a promising model for language instruction that meets the needs of today’s digital-native students.